Dinamika Komunitas Fitoplankton Pada Siang dan Malam Hari di Perairan Desa Sungsang Muara Sungai Musi, Sumatera Selatan - Fery Pratama; Rozirwan Rozirwan; Riris Aryawati (Faculty of Mathtmatics and Natural Sciences, 2019)
The Sungsang waters are often used by the surrounding community for water transportation, fishing and wash. The correlation of phytoplankton community with the physical-chemical parameters that can be used to determine the condition of the waters. The purpose of this research was to discuss the types of phytoplankton, analyze the community index and correlation between physical - chemical parameters in Sungsang waters. The research was had been done on November 2018, taking of samples and measurements was performed at 3 station points by tides at the day and night in 3 days. Taking of sampels that is phytoplankton and nutrient water samples, measurements of physical - chemical parameters that is DO, temperature, salinity, pH and current velocity, the correlation of phytoplankton community's with physical-chemical parameters are carried out by principal component analysis (PCA). The phytoplankton composition at night was found 39 genera from 4 classes, while during the day there were 41 genera from 5 classes. Percentage of phytoplankton composition class that is Bacillariophyceae (98.77%), Cyanophyceae (0.87%), Dinophyceae (0.29%), Chlorophyceae (0.055%) and Dictyochophyceae (0.014%). The abundance of phytoplankton is range between 298 - 2,533 cells/l with the diversity index of the dominant is medium category, the uniformity index of the dominant is high category and the dominance index of the dominant is low category. Based on the results of PCA for the correlation between phytoplankton communities with physical-chemical parameters during at day with the identifiers is uniformity index, DO, dominance index, phosphate, salinity and current, the identifiers at night is current, pH, nitrate, temperature, phosphate, DO, diversity index and uniformity index, for combined data day and night the identifiers is diversity index, phosphate, uniformity index, abundance, temperature, pH, dominance index and salinity.